2011
DOI: 10.1007/s00268-011-0994-x
|View full text |Cite
|
Sign up to set email alerts
|

Risk Factors for Splenic Injury During Colectomy: A Matched Case–Control Study

Abstract: Splenic flexure mobilization is the primary risk factor for splenic injury during colectomy, independent of other factors, such as higher ASA class, Charlson score, and nonelective surgery. Splenic injury during colectomy has an increased risk of death in both the short- and long-term.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
23
2
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(29 citation statements)
references
References 19 publications
1
23
2
1
Order By: Relevance
“…Previously‐identified risk factors for splenic injury have been largely reported from colorectal surgical literature. In one series, the single risk factor independently associated with increased risk of splenic injury was mobilization of the splenic flexure of the colon . Indications for colon surgery ranged from benign (diverticular disease) to malignant (colon and rectal carcinoma) etiologies.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previously‐identified risk factors for splenic injury have been largely reported from colorectal surgical literature. In one series, the single risk factor independently associated with increased risk of splenic injury was mobilization of the splenic flexure of the colon . Indications for colon surgery ranged from benign (diverticular disease) to malignant (colon and rectal carcinoma) etiologies.…”
Section: Discussionmentioning
confidence: 99%
“…Given the infrequency of this complication, few reports exist that specifically examine the relationship between iatrogenic splenectomy and adverse outcomes for patients treated with nephrectomy. Data regarding iatrogenic splenectomy in the urological setting are frequently taken from larger and more robust studies in the colon and rectal surgery literature . Although iatrogenic splenectomy among patients undergoing nephrectomy for renal tumors might be a rare adverse event, clinicopathological risk factors, such as tumor size, location and surgical approach, have yet to be investigated.…”
Section: Introductionmentioning
confidence: 99%
“…In laparoscopic low anterior rectal resection, the need to perform a complete total mesorectal excision coupled with low transection of the rectum make the whole operation technically demanding (7) . Moreover, the construction of a low colorectal anastomosis after SF mobilization allowing free descent of the left colon into the pelvis adds complexity to the procedure (2,3,10) and risk of iatrogenic injuries to spleen and retroperitoneal structures (14) . In the study conducted by Jamali et al (7) , a mail-survey of 35 experienced laparoscopic colorectal surgeons revealed that all colorectal procedures requiring SF mobilization scored high difficulty ratings.…”
Section: Discussionmentioning
confidence: 99%
“…1 This step is technically difficult and not without risk. There may be splenic trauma leading to bleeding and, therefore, the possible requirement to proceed to splenectomy, [2][3][4] which is associated with reduced 30-day and 5-year survival. 3 SFM is also associated with longer operative time regardless of surgery type.…”
mentioning
confidence: 99%
“…There may be splenic trauma leading to bleeding and, therefore, the possible requirement to proceed to splenectomy, [2][3][4] which is associated with reduced 30-day and 5-year survival. 3 SFM is also associated with longer operative time regardless of surgery type. 5,6 We hypothesised that the difficulty of SFM is related to the anatomical height of the splenic flexure (ie difficulty increases with distance from the midline).…”
mentioning
confidence: 99%